Examining ecosystem (dis-)services on liver fluke infection in rural Northeast Thailand - Yi-Chen Wang; Andrea Law; Jutamas Namsanor; Paiboon Sithithaworn (BMC, 2023)
Abstract Background The direct reliance of humans on and their interactions with freshwater ecosystems in the Lower Mekong Basin have given rise to parasitic infections, which is particularly prevalent in Northeast Thailand where raw fish consumption is practiced. This study examined the interactions between environments, ecosystem (dis-)services, human raw fish consumption habits, and raw fish dish sharing on liver fluke infection risk. Method Water fecal contents and the first intermediate snail host were sampled between June and September of 2019. One hundred twenty questionnaires were surveyed in two villages of different environmental surroundings, one next to a river and the other located inland, in Northeast Thailand. Multivariate regression analyses using linear mixed effect models assessed the influence of social, behavioral and perceptual factors on raw fish consumption frequency, willingness to avoid consumption and liver fluke infection status. Social network analysis compared the degree of raw fish dish sharing between the villages and assessed the probable influence of connections to fish procurement locations and sharing activities on liver fluke infection risk. Results High abundance of the first intermediate snail host and presence of fecal contamination in water could endanger both villages to ecosystem disservices of parasitic transmission. The river-side village relied more on provisioning ecosystem services than the inland village (29.7% vs. 16.1% of villages) to consume raw fish as their main source of protein. Males in both villages (64.5 and 40.4 days/year for the respective villages) are also likely to consume koi pla and pla som, higher risk fish dishes, more frequently than females (4.1 and 4.3 days/year for the respective villages). The consumption habits of both villages were driven mostly by deriving cultural ecosystem services. Participation in raw fish dish sharing activities significantly reduced the odds of an individual being willing to avoid the consumption (Odds ratio = 0.19). Network analysis suggested that river-side villagers had a more direct raw fish dish sharing interaction and they procured fish from multiple locations; these characteristics might potentially account for more liver fluke infected households in the village. Conclusion Villagers' raw fish consumption is driven by deriving cultural ecosystem services, and the geographic settings of the villages potentially affect villagers' fish procurement locations and infection risk. The findings underscore the linkages between villagers and their surrounding ecosystem environments as pertinent determinants for foodborne parasitic disease risk. Graphical Abstract